Broadcast protocols to support efficient retrieval from databases by mobile users - Datta, Anindya; VanderMeer, Debra E.; Celik, Aslihan; Kumar, Vijay (ACM transactions on database systems, 1999)
Mobile computing has the potential for managing information globally. Data management issues in mobile computing have received some attention in recent times, and the design of adaptive braodcast protocols has been posed as an important probllem. Such protocols are employed by database servers to decide on the content of bbroadcasts dynamically, in response to client mobility and demand patterns. In this paper we design such protocols and also propose efficient retrieval strategies that may be employed by clients to download information from broadcasts. The goal is to design cooperative strategies between server and client to provide access to information in such a way as to minimize energy expenditure by clients. We evaluate the performance of our protocols both analytically and through simulation.